An Experimental Study of the Long-Term Behaviour of Composite Beams with Trapezoidal Steel Sheeting - Moy, C.K.S.; Ostinelli, A.; Ranzi, G.; Ansourian, P. (Civil-Comp Press, 2013)
In steel framed building construction, it is common to have the slab cast on steel decking and the headed stud shear connectors welded through thin high-strength profiled sheeting to the top flange of the steel. They are economic because the profiled steel decking provides permanent and integral formwork to the concrete slab. Over recent years, deep open trapezoidal profiles have been developed which are able to span large distances when propped or unpropped between secondary beams in a flooring system when their troughs are orthogonal to the steel joists. Despite the extensive work carried out to evaluate the ultimate response of this form of construction, only limited work has been devoted to date on the long-term response of composite steel-concrete floor systems. This paper presents a study aimed at the evaluation of the long-term behaviour of composite steel-concrete beams designed with partial shear connection formed by a steel joist and a composite slab with trapezoidal steel sheeting. The results of an experimental programme are presented. One sample was designed as a secondary beam of a typical composite flooring system based on Australian guidelines with the low levels of degree of shear connection. The specimen was cast propped and was subjected to a sustained uniformly distributed load for a period of 10 months. Standard short- and long-term tests were carried out to obtain the relevant material properties of both steel and concrete. The experimental results were modelled by means of analytical solutions. The accuracy of the numerical predictions is discussed based on the specified material properties and the reported experimental data.